2020
DOI: 10.7150/jca.41437
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a-5p promotes cholangiocarcinoma cell proliferation through targeting SOCS3

Abstract: Background: MicroRNAs (miRNAs) play important roles in the occurrence and development of cancers. In this project, we aimed to explore the role and molecular mechanism of mir-30a-5p in cholangiocarcinoma (CCA). Materials and Methods:The expression profile and clinical significance of miR-30a-5p in CCA patients were investigated in 31 ICC and 52 ECC patients respectively. The role and mechanism of miR-30a-5p in CCA cells were investigated by up-regulating and inhibiting miR-30a-5p expression in vitro functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In several studies, BCL2 has been reported to act as a target gene of multiple miRNAs, including miR‐153, miR‐136 and miR‐365 . BCL2 has also been elucidated to be a target gene of miR‐15b in condylar hyperplasia and liver cancer . miR‐15b has been shown to play a role in the development of multidrug resistance in gastric cancer cells, at least in part by modulation of apoptosis via targeting BCL2 .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, BCL2 has been reported to act as a target gene of multiple miRNAs, including miR‐153, miR‐136 and miR‐365 . BCL2 has also been elucidated to be a target gene of miR‐15b in condylar hyperplasia and liver cancer . miR‐15b has been shown to play a role in the development of multidrug resistance in gastric cancer cells, at least in part by modulation of apoptosis via targeting BCL2 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miRNAs may be used as tumor suppressor genes to regulate the pathophysiological process of CAA. On the contrary, Zhang et al have found that the expression of miR-30a-5p was increased in both CCA tissues and cells, and it could promote the proliferation of CCA cells by inhibiting SOCS3 [ 28 ]. The mechanisms of the above studies all focused on that miRNAs can inhibit, attenuate, or eliminate the expression of downstream genes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is involved in the pathophysiological process in many diseases by negative regulation of target genes [15].To found the potential target gene of miR-27a-3p in CCA, we used two independent algorithms, TargetScan (www.targetscan.org/), and mirbase (www.mirbase.org/), and found that ING5 could be a potential gene of miR-27a-3p target (Fig. 4A).…”
Section: Ing5 Directly Target Mir-27a-3pmentioning
confidence: 99%